Does the activity of passenger transport have growth potential for the sustainable development of Constanta County? - Stan, Mari-Isabella (Technium Social Sciences Journal, 2022)
Transport is a vital sector with a major impact on social and environmental well-being, both in cities and in rural areas. The sustainable development of urban and rural communities depends mainly on the dynamics of the economic activity, transport having a special importance for the local economy, without which human activities would be impossible to organize and carry out. On the one hand, the companies need transport in order to produce and deliver their goods and services, and on the other hand, people need transport in order to get to work, for getting supplies, for education, tourism, recreation, and leisure and other daily activities. Considering these multiple perspectives, we have considered it appropriate to analyze the activity of the companies whose object of activity is passenger land transport at the level of Constanta County based on representative economic and financial indicators, exploring the possible determining factors which influence this sector in the context of the interest for the sustainable development of Constanta County.